Pelaksanaan Tanggung Jawab Negara Peru Sebagai Negara Penerima Dalam Melindungi Diplomat Asing Berdasarkan Konvensi Wina 1961: Studi Kasus Penembakan Diplomat Indonesia Di Peru - varik farsyak; Nasriel ikhsan; Qaulan Sadidah; Salsabilah Putri Maesa Daulay (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study analyzes the obligations of recipient countries to protect foreign diplomats based on the 1961 Vienna Convention and its implementation in the case of the shooting of Indonesian diplomats in Peru. The method used is normative legal research with a statutory and case approach. The results of the study indicate that Peru is normatively bound by the obligation to guarantee the security, freedom, and dignity of diplomats through the principle of inviolability as stipulated in Articles 22 and 29 of the 1961 Vienna Convention. However, in practice there are indications of inconsistencies between norms and implementation, particularly in the aspect of preventing security threats. The shooting incident has the potential to give rise to international responsibility of the state based on the principle of state responsibility in ARSIWA 2001 if negligence is proven. Therefore, the effectiveness of diplomat protection is highly dependent on the ability of the recipient country to implement its obligations in a preventive and responsive manner.